Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1029/2011jd017123
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between lightning flash rates and radar reflectivity vertical structures in thunderstorms over the tropics and subtropics

Abstract: [1] Relationships between the vertical profile of radar reflectivity and lightning flash rates are investigated using 13 years of Tropical Rainfall Measuring Mission (TRMM) observations during 1998-2010. First the Radar Precipitation Features (RPFs) are defined by grouping raining areas detected by the TRMM Precipitation Radar (PR). Then the characteristics of radar reflectivity and lightning flash rate are calculated in each RPF using PR and Lightning Imaging Sensor (LIS) observations. Using these RPFs, temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
139
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(162 citation statements)
references
References 70 publications
(77 reference statements)
15
139
0
3
Order By: Relevance
“…Liu et al (2007) observed the large areas of cold clouds over West Pacific Ocean, whereas central Africa, Argentina, and India consist deeper and more horizontally extensive PFs, and Land dominated areas consist higher 20 dBZ area above the freezing level (Liu et al, 2008). Liu et al (2012) observed the relationship between lightning flash rates and vertical structure of thunderstorms. Yuan and Qie (2008) explored the south China sea before and after the onset of the summer monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2007) observed the large areas of cold clouds over West Pacific Ocean, whereas central Africa, Argentina, and India consist deeper and more horizontally extensive PFs, and Land dominated areas consist higher 20 dBZ area above the freezing level (Liu et al, 2008). Liu et al (2012) observed the relationship between lightning flash rates and vertical structure of thunderstorms. Yuan and Qie (2008) explored the south China sea before and after the onset of the summer monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…RPFs are features defined using the Version 7 TRMM Precipitation Radar (PR) rainfall retrieval and are required to have contiguous pixels with near-surface precipitation (as in Liu et al [2012]). For this study, to eliminate noise, we examined RPFs with at least four contiguous pixels.…”
Section: Trmm Database: Congo and Central Pacific As Archetypesmentioning
confidence: 99%
“…Low passive microwave brightness temperatures (37 and 85 GHz, especially) indicate the extent of ice scatterers in the column, while high maximum heights of high reflectivity (e.g., 40 dBZ) indicate the height to which graupel is lofted. Lightning flash rates are often used as a proxy for updraft speed and/or convective intensity [Nesbitt et al, 2000;Cecil et al, 2005;Zipser et al, 2006;Liu et al, 2008Liu et al, , 2012. Strong updrafts favor both graupel and supercooled liquid water in the mixed phase region, both of which are required by the widely accepted noninductive ice-ice collision mechanism of charge separation [Takahashi, 1978].…”
Section: Introductionmentioning
confidence: 99%
“…The result is net accumulation of opposite charge in different parts of the thundercloud. This has been shown to be a realistic theory through a combination of laboratory, field measurement and satellite studies (Williams, 1989;Blyth et al, 2001;Petersen et al, 2005;Saunders, 2008;Deierling et al, 2008;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%